Lessons Learned From COVID-19 Contact Tracing During a Public Health Emergency: A Prospective Implementation Study - Shelby, Tyler; Schenck, Christopher; Weeks, Brian; Goodwin, Justin; Hennein, Rachel; Zhou, Xin; Spiegelman, Donna; Grau, Lauretta E.; Niccolai, Linda; Bond, Maritza; Davis, J. Lucian (Frontiers in Public Health, 2021)
Background: Contact tracing is a core element of the public health response to emerging infectious diseases including COVID-19. Better understanding the implementation context of contact tracing for pandemics, including individual- and systems-level predictors of success, is critical to preparing for future epidemics. Methods: We carried out a prospective implementation study of an emergency volunteer contact tracing program established in New Haven, Connecticut between April 4 and May 19, 2020. We assessed the yield and timeliness of case and contact outreach in reference to CDC benchmarks, and identified individual and programmatic predictors of successful implementation using multivariable regression models. We synthesized our findings using the RE-AIM implementation framework. Results: Case investigators interviewed only 826 (48%) of 1705 cases and were unable to reach 545 (32%) because of incomplete information and 334 (20%) who missed or declined repeated outreach calls. Contact notifiers reached just 687 (28%) of 2437 reported contacts, and were unable to reach 1597 (66%) with incomplete information and 153 (6%) who missed or declined repeated outreach calls. The median time-to-case-interview was 5 days and time-to-contact-notification 8 days. However, among notified contacts with complete time data, 457 (71%) were reached within six days of exposure. The least likely groups to be interviewed were elderly (adjusted relative risk, aRR 0.74, 95%CI 0.61-0.89, p=0.012, vs. young adult) and Black/African-American cases (aRR 0.88, 95%CI 0.80-0.97, pairwise p=0.01, vs. Hispanic/Latinx). However, ties between cases and their contacts strongly influenced contact notification success (Intraclass Correlation Coefficient (ICC) 0.60). Surging caseloads and high volunteer turnover (case investigator n=144, median time from sign-up to retirement from program was four weeks) required the program to supplement the volunteer workforce with paid public health nurses. Conclusions: An emergency volunteer-run contact tracing program fell short of CDC benchmarks for time and yield, largely due to difficulty collecting the information required for outreach to cases and contacts. To improve uptake, contact tracing programs must professionalize the workforce; better integrate testing and tracing services; capitalize on positive social influences between cases and contacts; and address racial and age-related disparities through enhanced community engagement.